Bridging the Gap between Theory and Practice of Inclusion in the United Arab Emirates - AlGhawi, Mariam Ali Juma Khalfan (2007)
Inclusion is an international phenomenon and a world wide movement which means catering for students with special needs within the regular classroom with the appropriate support. Educating a student with special needs in the United Arab Emirates (UAE) is relatively new. The country itself is a fairly new developing country which was declared around thirty six years ago. The UAE has made significant progress in different areas including education. Inclusion of students with special needs in the mainstream schools is a new approach in education which the country is piloting now. Students with special needs used to be served in segregated special centres before the declaration of the new Federal Law no. 29/2006 for the rights of disabled persons which includes education as a fundamental right. This research is aims to bridge the gap between theory and practice in the inclusive educational approach the country is currently adopting by presenting a set of recommendations which may improve the provision for students with special needs in the country. The research was conducted using various data collection methods. A triangulation of methods was used to ensure the validity of the data which included observation, interview and documents review. The finding of the research indicates that there is a huge gap between the theory of inclusion presented by the newer federal law and the practice where inclusion is implemented in some schools. Moreover, schools were found to be not ready for implementing inclusion and furthermore, attitudes are seen to be negative towards special needs. Additionally it was found that the educational system is a ridge and only caters for students who fall under the normal range. In conclusion, the research emphasised the importance of preparing schools and the community before implementing the law. Moreover, the research offers a set of recommendations based on the findings of the research and the literature of inclusive education to improve the provision of special needs in the country.